A word from our Editor-in-Chief: NONCONVENTIONAL TECHNOLOGIES - A GREAT BOOK (Nonconventional Technologies Review, 2025)
Dimensional processing technologies known as "Concentrated Energy Processing Technologies", "Nonconventional Technologies" or "Alternative Technologies" can be characterized by exceptional dynamics of use, perhaps the highest of all technologies applied in machine building. Practically, these new technologies have gone through all the phases from their "invention" to their wide industrial use in only about 65 years, currently becoming alternative technologies, complementary to classical technologies.